2015
DOI: 10.1590/1982-0194201500036
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas de depressão e fatores intervenientes entre enfermeiros de serviço hospitalar de emergência

Abstract: Objective: To verify if nurses from the emergency hospital services had depressive symptoms, identifying intervening factors and analyzing perception about the psychic suffering and its influence on care provided. Methods: Cross-sectional study, conducted with nurses of emergency hospital services. The research instrument was a semi-structured questionnaire with sociodemographic variables and psychometric scales for the assessment of depression. For statistics, the Fisher exact test was used. Results: A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
1
5
0
18
Order By: Relevance
“…The work demands are related both to the work organization and to issues involving the end of the lives of patients, which is something that absorbs all one's energy, as is emphasized in the fi rst account above, causing stress and increasing the number of medical certifi cates for depression, as evidenced by the second and third accounts. Corroborating the present study's fi ndings, a study conducted by Oliveira, Mazzaia, and Marcolan (2015) of nurses that work in a hospital emergency department found that 90% of the ED professionals had fallen ill due to depression, an extremely signifi cant number. Such data warrant consideration and interventions aimed at improving the working conditions and mental health of such professionals.…”
Section: Health Professionals' Mental Healthsupporting
confidence: 77%
“…The work demands are related both to the work organization and to issues involving the end of the lives of patients, which is something that absorbs all one's energy, as is emphasized in the fi rst account above, causing stress and increasing the number of medical certifi cates for depression, as evidenced by the second and third accounts. Corroborating the present study's fi ndings, a study conducted by Oliveira, Mazzaia, and Marcolan (2015) of nurses that work in a hospital emergency department found that 90% of the ED professionals had fallen ill due to depression, an extremely signifi cant number. Such data warrant consideration and interventions aimed at improving the working conditions and mental health of such professionals.…”
Section: Health Professionals' Mental Healthsupporting
confidence: 77%
“…Supportive nursing management was thought likely to result in better diabetes education and care among nurses, while lack of attention to nurses’ own problems (e.g., workload) might have the opposite effect (Farsi, Dehghan, Negarandeh, & Broomand, ). Nurse managers have a role to play in creating a positive work environment, influencing nurses by motivating and encouraging them to improve their diabetes knowledge, involving nurses in policymaking, especially where policies affect nursing staff directly and may enhance or detract from nurses’ diabetes knowledge (de Oliveira, Mazzaia, & Marcolan, ). Effective inter‐ and intraprofessional communication and collaboration and diabetes knowledge exchange could be effective; even the simple availability of printed learning materials, and increasing institutional resources and support for continuing diabetes education and training (Gerard et al., ; Modic et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Destacam-se dados de estudo com as mesmas escalas psicométricas que apontaram prevalência de 95,6% da sintomatologia depressiva em enfermeiros de unidades de emergência (11) .…”
Section: Análise E Discussãounclassified